Translators as mediators to mend the psychological gap between source text and target text: A corpus-based study on the Chinese English translation of modal verbs in the Chinese Report on the Work of the Government (2000-2022). - Xujun Tian (PLoS ONE)
This study examines the role of translators as mediators in bridging the psychological gap between source text (ST) and target text (TT) through a corpus-based analysis of Chinese English translation of modal verbs in the Chinese Report on the Work of the Government from 2000 to 2022. The research reveals that translators frequently modulate high-value Chinese modals into medium or low-value English equivalents. This strategic modulation, along with the use of explicitation and implicitation, reflects the translators' efforts to balance source text fidelity with target text acceptability. The findings underscore the translators' role in adapting authoritative Chinese political discourse to align with expectations of the international audiences, thereby facilitating effective cross-cultural communication. This study contributes to translation studies by providing insights into the translation of modality in political texts and emphasizing the critical role of translators in mediating linguistic and cultural differences.